Incidence and prognosis implications of long term left ventricular reverse remodeling in patients with dilated cardiomyopathy. (15th January 2016) - Ruiz-Zamora, Isabel; Rodriguez-Capitan, Jorge; Guerrero-Molina, Alicia; Morcillo-Hidalgo, Luis; Rodriguez-Bailon, Isabel; Gomez-Doblas, Juan Jose; de Teresa-Galvan, Eduardo; Garcia-Pinilla, Jose Manuel
Abstract: Background: Left ventricular reverse remodeling (LVRR) in dilated cardiomyopathy is poorly known within the context of current therapeutic approach. Our goal is to describe the present incidence of LVRR, the factors able to predict it and the long term prognosis of these patients. Methods and results: We performed a retrospective analysis of a cohort or 387 consecutive outpatients. Mean follow-up was 50.4 ± 28.4 months. Sustained LVRR occurred in 57.6% of patients. The number of coronary arteries with severe stenosis (HR 0.69, 95% CI 0.55–0.86; p = 0.001), New York Heart Association Functional Class (NYHA FC) (HR 0.39, 95% CI 0.27–0.54; p < 0.001) as well as the severity of mitral regurgitation (MR) at the end of follow-up (HR 0.42, 95% CI 0.30–0.58; p < 0.001) and the time until first event (HR 1.02, 95% CI 1.01–1.03; p < 0.001) were independent predictors of left ventricular ejection fraction improvement. LVRR was tightly related to prognosis due to the fact that both improvement in cardiac function achieving normal or slightly impaired LVEF (HR 0.31, 95% CI 0.17–0.56; p < 0.001) and shorter time to achieve LVRR (HR 0.99, 95% CI 0.98–0.99; p = 0.017) formed part of the best model for predicting events in DCM. Conclusion: More than half of the patients showed sustained LVRR associated with a significantly better prognosis. Fewer numbers of coronary arteries with severe stenosis, milder NYHA FC and the absence of significant MR at the end of follow-up as well as longer event free period formed a simple model to prognosticate LVRR. LVRR and the time to achieve it were strongly related to long term prognosis in patients with DCM.